Important considerations for the validation of QSAR models for in vitro mutagenicity. (20th October 2018) - Cayley, Alex; Fowkes, Adrian; Williams, Richard V
Abstract: While high-level performance metrics generated from the validation of quantitative structure–activity relationship (QSAR) systems can provide valuable information on how well these models perform and where they need to be improved, they require appropriate interpretation. There is no universal performance metric which will answer all of the questions a user might ask relating to a model, and therefore, a combination of metrics should usually be considered. Furthermore, results may vary according to the chemical space being used to validate a model, and, in some cases, it may be the validation data which is lacking or ambiguous rather than the prediction being made. Finally, users also need to consider the interpretability of the predictions being made, alongside the accuracy of the predictions. In this paper, we will discuss these important considerations in more detail within the context of the results obtained at Lhasa Limited as part of the National Institute of Health Sciences (NIHS) QSAR challenge project.